2014
DOI: 10.1016/j.jvs.2013.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral ischemic lumbosacral plexopathy from chronic aortoiliac occlusion presenting with progressive paraplegia

Abstract: Spinal cord ischemia is rare but causes significant morbidity and mortality. Spinal cord ischemia has been reported after open and endovascular interventions of the thoracic and abdominal aorta, and, rarely, acute occlusion of aorta from in situ thrombosis or acute embolic occlusion. Acute interruption of the critical blood supply to the spinal cord or root contributes to this devastating neurologic deficit. However, gradually worsening lumbosacral plexopathy and consequent paraplegia related to chronic aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
9
0
3
Order By: Relevance
“…There are other examples of similar events in aneurysmal patients following bypass surgery [ 7 11 ]. Iliopoulos et al reported eleven patients of aortic aneurysm with hypogastric artery ligation.…”
Section: Discussionmentioning
confidence: 99%
“…There are other examples of similar events in aneurysmal patients following bypass surgery [ 7 11 ]. Iliopoulos et al reported eleven patients of aortic aneurysm with hypogastric artery ligation.…”
Section: Discussionmentioning
confidence: 99%
“…La ketamina tiene propiedades analgésicas y antidepresivas y ha sido usada en forma segura y efectiva como analgésico para el dolor agudo posoperatorio, el dolor crónico y el dolor con componente neuropático (16); este es un medicamento antagonista no competitivo en el sitio de unión de la fenciclidina de los receptores N-metil-D-aspartato (NMDA) localizados en el sistema nervioso, por lo cual disminuye su tiempo de apertura y reduce el fenómeno de sensibilización central. Asimismo, no tiene los efectos adversos de otros medicamentos como los AINES a nivel gastrointestinal y renal, preserva los reflejos protectores de la vía aérea superior, aumenta la capacidad pulmonar y tiene menor riesgo de depresión respiratoria (17).…”
Section: Conclusãounclassified
“…Imaging revealed occlusion of the infrarenal abdominal aorta, and bilateral common iliac and right external iliac arteries consistent with aortoiliac occlusive diseases. Kim et al () presented an extremely rare case of gradually worsening lumbosacral plexopathy with consequent paraplegia related to aortoiliac occlusion. The patient presented with symptoms diagnostic of lumbosacral plexopathy, including gradually worsening bilateral lower extremity weakness, hyporeflexia, and dysesthesias.…”
Section: Clinical Presentation With Relation To Anatomymentioning
confidence: 99%